2021
DOI: 10.1007/s40674-021-00186-x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Treatment of Anti-MDA5 Rapidly Progressive Interstitial Lung Disease

Abstract: Purpose of the Review Idiopathic inflammatory myopathies are a heterogeneous group of autoimmune disorders. The presence of different autoantibodies allows clinicians to define distinct phenotypes. Antibodies against the melanoma differentiation-associated protein 5 gene, also called anti-MDA5 antibodies, are associated with a characteristic phenotype, the clinically amyopathic dermatomyositis with rapidly progressive interstitial lung disease. This review aims to analyze the different pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 74 publications
(67 reference statements)
0
21
0
4
Order By: Relevance
“…A retrospective study in Japan reproduced these results; however, they reported frequent cytomegalovirus reactivation secondary to severe immunosuppression [13]. For patients unable to tolerate calcineurin inhibitors, mycophenolate mofetil and biological therapies may be considered [11].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…A retrospective study in Japan reproduced these results; however, they reported frequent cytomegalovirus reactivation secondary to severe immunosuppression [13]. For patients unable to tolerate calcineurin inhibitors, mycophenolate mofetil and biological therapies may be considered [11].…”
Section: Discussionmentioning
confidence: 86%
“…Aggressive and early treatment with the use of multiple immunosuppressive agents is essential in the management of CADM-ILD. First line therapy involves high-dose glucocorticoids combined with calcineurin inhibitors, with or without cyclophosphamide [11]. A multicenter prospective study in Japan found that patients treated initially with a combination of high-dose glucocorticoids, calcineurin inhibitors, and cyclophosphamide had a 6-month survival rate of 89%, compared to 33% in patients treated with a step-up strategy starting with high-dose glucocorticoids [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 However, occasionally the disease is refractory, rapidly progressive, and resistant to hormonal and immunosuppressive therapies. 15 As a result, it is necessary to develop alternative drug therapies based on the current understanding of ILD pathogenesis and the role of the JAK/STAT pathway in it. The existing knowledge and scientific rationale on the efficacy of JAK inhibitors (JAKi) suggest that they may provide clinicians with a more precise treatment strategy for reducing interstitial inflammation thereby preventing the progression of fibrosis and the continuous deterioration of lung function.…”
Section: Introductionmentioning
confidence: 99%